Hypercontent: Today's Learning Solutions - Novita Efendi; Anisa Nurjanah; Dina Fitria Handayani; Titiek Fujita Yusandra; Mona Amelia (CV. Creative Tugu Pena, 2026)
The need for innovative language learning materials that comprehensively combine theory and practice is the reason for this research. Conventional learning media, which are still widely used, are more textual and less interactive, and do not fully support independent learning and active student participation. Engaging, flexible, and interactive learning media are needed with the advancement of digital technology. Therefore, the purpose of this research is to develop a hypercontent-based e-module as a digital learning medium that allows the integration of various forms of content such as text, images, audio, video, and links to external learning resources. The EDDIE development model was used, which includes the stages of evaluation, design, development, implementation, and final evaluation. The research subjects consisted of 55 students who underwent a module feasibility test and needs test. Initial observations indicated that a digital-based learning module that supports independent language learning was needed by 92 percent of students. Subject matter experts (72.6%) considered it feasible, media experts (82.9%) considered it very feasible, and learning design experts (91.25%) considered it very feasible. In addition, the results of the one-to-one test on three students obtained an average score of 97.47% (very appropriate). The effectiveness test using the t-test produced a t-count value of -10.130 < t-table -2.2, so H₀ was rejected. This indicates that E‑Hypercontent-based modules are very effective for use as independent learning materials in language learning. Thus, the development of E‑This module can improve students' understanding, strengthen digital literacy, and create a more active and contextual learning experience in today's era of educational technology.